2023
DOI: 10.3390/jmse11071391
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on Cavitation Jet in Circular Arc Curve Chamber Self-Excited Oscillation Nozzle

Abstract: In order to improve the cavitation performance of the self-excited oscillation nozzle (SEON), a novel SEON with a circular arc curve chamber was designed by changing the chamber wall profile of the SEON. The performance of the circular arc curve chamber SEON was studied numerically. Taking the vapor volume distribution and the vapor volume fraction as the evaluation indexes, the influences of the chamber wall profile on the cavitation performance of the circular arc curve chamber SEON were analyzed. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In order to validate the accuracy of this fitting model, numerical simulations of the optimized structure were carried out, resulting in an actual peak gas-phase volume fraction of 32.41%. The peak gas-phase volume fraction of the optimized nozzle was significantly improved; compared to the same type of Helmholtz single-chamber nozzle [14], the gas-phase volume fraction increased by 189% and the relative error between the predicted and simulated values obtained by the response surface method under the same operating conditions was 2.04%. This small error confirms the reliability and accuracy of the model obtained by the response surface method.…”
Section: Response Surface Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…In order to validate the accuracy of this fitting model, numerical simulations of the optimized structure were carried out, resulting in an actual peak gas-phase volume fraction of 32.41%. The peak gas-phase volume fraction of the optimized nozzle was significantly improved; compared to the same type of Helmholtz single-chamber nozzle [14], the gas-phase volume fraction increased by 189% and the relative error between the predicted and simulated values obtained by the response surface method under the same operating conditions was 2.04%. This small error confirms the reliability and accuracy of the model obtained by the response surface method.…”
Section: Response Surface Analysismentioning
confidence: 89%
“…Chen et al [13] confirmed through numerical simulations that cavitation jet corrosion of steel is primarily due to the generation of high-strength shock waves and instantaneous high temperatures when cavitation bubbles collapse. Dong et al [14] modified the cavity wall contour of the Helmholtz nozzle into a circular arc shape, resulting in a 16.9% increase in turbulent flow energy. Yang et al [15] captured the growth, shedding, and collapse of cavitation in three nozzle jets using high-speed photography, finding good agreement between experimental images and predicted model images.…”
Section: Introductionmentioning
confidence: 99%